Caspase interaction of anti-apoptotic Livin as well as the Vacuolar ATPase (V-ATPase) and structural insights into the subunit d and a of the yeast V-ATPase - Thaker, Youg Raj (2009)
Apoptosis is a critical process to remove the non-functional and redundant cells regulated by pro- and anti-apoptotic factors. Perturbation of balance between pro- and anti-apoptotic components is the leading cause of several physiopathological conditions such as neurodegenerative and cancer malignancies. Here, the pro-apoptotic cellular protein, ARTS as well as an anti-apoptotic protein, Livin, a family member of inhibitor of apoptosis have been studied. Results showed that ARTS is not the target of Livin E3 ligase activity in apoptotic cells co-expressing ARTS and Livin. In turn, Livin was found to undergo cleavage in ARTS promoted apoptosis which was independent of its self-ubiquitination activity, normally observed in healthy cells. The exhaustion of Livin during ARTS-promoted apoptosis could partially be suppressed by the caspase inhibitors, implying a possible role of caspases concomitant with high active caspase 7 levels found in ARTS-promoted staurosporine-induced apoptosis. Not only Livin, caspase do cleave several important cellular components during apoptosis and here, I have identified subunit d of V-ATPase as a new target of caspase 3. V ATPases do play critical role in health and disease by maintaining proper acid/base balance pH. Additionally, homogenous protein preparation of yeast subunit d protein was used to determine its first low resolution shape by small angle X-ray spectroscopy (SAXS), revealing two distinct domains of 6.5 nm and 3.5 nm widths forming a “boxing glove” shape. Using previously solved low resolution structure of VO domain as a template, subunit d could be assigned inside the VO, allowing its clear localization on the top of VO domain of V-ATPase. Moreover, biochemical approaches of fluorophore labeling, tryptic digestion and MALDI-TOF analysis led to the identification of a cysteine bridge between Cys36 and Cys329.